Preserving user‐participation for insecure network communications with CAPTCHA and visual secret sharing technique. Issue 2 (1st June 2013) - Lee, Jung‐San; Hsieh, Ming‐Huang
Abstract : How to provide confidential communications for involved users is always a critical challenge in designing a network system. Especially, people must face malicious attacks while surfing over an insecure network, such as brute force attack, password guessing attack, DOS attack, masquerade attack, replay attack or Trojan horse risk. Let these attacks be surveyed in more detail, and the authors can find the fact that the intruder usually launches these through thousands of trials without the interaction between the user and server. Of course, these trials are performed via bots. Thus, this study aims to develop a robust system that can guarantee the user‐participation essential in the communication. That is, if the involved participants cannot prove that they are human beings, then the system will terminate the connection to prevent the attack. To achieve this, the authors apply the techniques of CAPTCHA and visual secret sharing into this system. Aside from proving the correctness of the authentication between the involved participants, the authors have conducted experiments to demonstrate the practicability of the proposed system.